Are there “Magic Bullets” for cancer theraphy - Seow, Heng Fong (Universiti Putra Malaysia Press, 2011)
Despite continuing intensive research, cancer is still a devastating disease with high mortality rates. However, progress made in understanding the behavior of tumour cells has led to advances in the creation of ‘magic bullets’ for treating cancer as exemplified by imatinib, an inhibitor that targets an oncogenic kinase, namely, bcr-abl. This article will focus on the seminal discoveries made in oncogenes, growth factor receptors and tyrosine phosphorylation and contributions from my research on signal transduction, adoptive immunotherapy and drug discovery. Signal transduction is a process whereby a cascade of proteins is activated inside the cell causing the cancer cell to grow uncontrollably and spread to other parts of the body. By blocking the signals with molecular-targeted drugs, the cancer cell growth can be controlled. The success of molecularly-targeted drugs depends on the target and knowledge of the signal transduction network. Due to the limited information on tumours available in Malaysia, we set out to determine the incidence of expression of proteins such as the epidermal growth factor receptor (EGFR), phosphatidyl-inositol-3-kinase (PI3K), pTEN, Akt and downstream targets such as β-catenin, pBAD, pGSK, pmTOR and pFHKR, by immunohistochemistry. This can provide insights into the possible mechanism of survival of colorectal, breast and nasopharyngeal carcinoma cells. The contributions of activating mutations such as PI3K in colorectal, breast and nasopharyngeal carcinoma were also compared. This approach revealed the potential therapeutic targets relevant to our population. In the second phase of the research program, we attempted to isolate inhibitors of signal transduction from soil-derived Actinomycetes . The ability of natural compounds purified from extracts of soil-derived Actinomycetes (genus Streptomycetes) to induce apoptosis, cytotoxic and cell cycle effects were also measured. This led to the discovery of the ability to arrest cells in the G1 phase in a breast cancer cell line, MCF-7. Further, the synergistic effect with a PI3K inhibitor was also revealed. Another approach to cancer treatment is adoptive immunotherapy. Conditions for the generation of cytotoxic CD8+ T lymphocytes with recognition for HER2-peptide specific and Epstein Barr viral protein and latent membrane protein-2 (LMP-2) were established to obtain cells for treating breast and nasopharyngeal carcinoma patients. The existence of cells with T regulatory cell phenotype was detected in breast and nasopharyngeal carcinoma. An alternative state of the art approach using mesenchymal stem cells for cancer therapy was also attempted. Subsequently, the immunomodulatory effects of umbilical mesenchymal stem cells was demonstrated with K562, an undifferentiated erythromyeloblastoid leukemia cell line. Lastly, the development of molecular diagnostic tests for ten species of Candida species was achieved. Monoclonal antibodies against Candida glabrata and Aspergillus fumigatus were also produced. In summary, we have successfully demonstrated the aberrations of the signal transduction pathway in primary breast, colorectal and nasopharyngeal carcinoma. This study has given us an insight into the relevant biomolecules in the cascade. Results from the nasopharyngeal carcinoma tissues revealed that the PI3K/Akt/mTOR pathway is not a linear pathway. The potency of the natural compound for cancer treatment will need to be tested on animal models. The second approach of harnessing the immune system showed promising results. The effectiveness of the cytotoxic T cells and mesenchymal stem cells generated will need to be tested on animal models. Thus, further work is warranted to improve treatment outcomes for cancer patients